GENETIC VARIABILITY AND MOLECULAR EVOLUTION OF THE IRAQI DATE PALM CULTIVARS USING INTERNAL TRANSCRIBED SPACER 1 (ITS1) REGION OF NUCLEAR RIBOSOMAL DNA - Hawash , Mohammed M.; Al-Shamma , Laith M.J. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
This study was aimed to investigate genetic diversity of nine Iraqi date palm cultivars (Phoenix dactylifera L.), two of them were propagated by tissue culture tiqneque. The variation in GC content in the ITS1 region was recorded at (52–53%) with an average of (52.7). The data suggests that transitions have a lower frequency compared to transversions in this region, where the overall bias R for transition/transversion has been estimated at (0.661). The aligned sequences associated with internal transcribed spacer 1 (ITS1) showed intraspecific variation, and the matched sequences enabled the identification of all cultivars studied as haplotypes. Phylogenetic trees constructed using distance-based ''neighbour-joining'' (NJ) and ''maximum parsimony'' (MP) techniques provided strong evidence for the independent structure of the considered accessions. Tests of molecular evolution reveal that the internal transcribed spacer 1 (ITS1) evolved in accordance with a precise neutrality paradigm. In a population predicted to be in equilibrium after the 6th generation, suggesting a recent demographic expansion in the Iraqi date palm population.